An RNA-based toolbox to advance cellular computing. (Research'eu results magazine)
Scientists from Germany, France and Austria have successfully programmed cellular networks and community behaviour of bacteria using newly engineered 'RNA based devices' (RNAdevs)-small molecular modules that regulate gene expression and function mainly based on ribonucleic acid sequences. The resulting toolbox opens the door to various applications in white biotechnology and medicine.